THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITY AND BRAND EQUITY ON CUSTOMER RESPONSE TO SKINCARE PRODUCTS: Pengaruh Aktivitas Sosial Media Marketing dan Ekuitas Merek terhadap Respon Customer Pada Produk Skincare - Hanifah Wirastuti Wirawan; Gesit Thabrani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study analyzes the impact of social media marketing activities (SMMA) on brand equity and consumer response in the skincare product. Customer responses in this research are divided into 2, namely: E-Wom and commitment. Customer response itself is the customer's response to the products or services offered by the Company regarding the products used. Customer response itself is encouraged because of the social media marketing activity carried out by the Company which aims to increase brand awareness and brand image of the company in order to get a positive response. from consumers. The research survey was conducted on 200 consumers who use social media managed by the Cosrx brand, and the data was analyzed through structural equation modeling using the Smart PLS v.4.0.9.9 application. The research results show that trends are one of the most important components of SMMA and SMMA in Cosrx skincare has a significant impact on brand awareness and brand image. Apart from that, the research results also show that brand awareness and brand image significantly influence E-Wom and commitment. It is hoped that the results of this research can be used as fundamental data in developing SMMA strategies for the beauty industry, in particular by investigating the relative importance of each SMMA component and analyzing the impact of SMMA.